(untitled) (Journal of Hama University, 2021)
The Labour Legislator has restricted the right of the employer to terminate an indefinite employment contract on the basis of the need to observe two concurrent conditions. The first is objective, namely, the existence of the justified reason for the dismissal of the worker, and the second is procedural and is reflected in the notification of the employee within a specified period of time before the termination of his contract. And since the Labour Legislator has restricted the employer’s right to terminate by taking into account both substantive and procedural requirements, this order will lead to the association of both the substantive officer here (economic reason) who is justified for layoffs with the procedural officer (notification condition). And since the economic cause would result in the existence of a material impact on the enterprise through the cessation or restructuring of its activity, and a legal effect on the contract through its termination, the employer would be required to notify the employee of such termination as has been done in jurisprudence, legislation and the judiciary.This fact has led to a legal imbalance between legal controls, both substantive and procedural. This imbalance, in turn, has led to the establishment of labour relations away from the principle of fairness and the balancing of the interests of the parties, both workers and employers, since it will not be possible to establish such a principle, unless those legal controls that are compatible with their substantive and procedural aspects are compatible.Therefore, the study examined the compatibility of the termination notice requirement with the economic justification for layoffs. The study concluded with results, the most important of which is the existence of a clear legislative contradiction between the legal provisions related to notification Termination and the legal provisions related to the justified economic reason for terminating the worker’s contract and discharging him. In addition, this contradiction resulted in an imbalance between the employer who represents the economic side of the enterprise and the worker representing the social aspect of the enterprise.